2016
DOI: 10.1123/jsep.2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

He Dies, He Scores: Evidence That Reminders of Death Motivate Improved Performance in Basketball

Abstract: This research applied insights from terror management theory (TMT; Greenberg, Pyszczynski, & Solomon, 1986) to the world of sport. According to TMT, self-esteem buffers against the potential for death anxiety. Because sport allows people to attain self-esteem, reminders of death may improve performance in sport. In Study 1, a mortality salience induction led to improved performance in a "one-on-one" basketball game. In Study 2, a subtle death prime led to higher scores on a basketball shooting task, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Specifically, after MS (vs. control) these individuals squeezed a hand dynamometer (which measures grip strength) harder than prior to MS. MS clearly made these individuals put more effort into this goal-relevant task. Other work has similarly shown that MS enhances basketball performance [36] and improves performance on academic tasks (e.g., reading comprehension) [37,38]. Taken together, this work suggests that the awareness of death may underlie the motivation to excel and is beneficial for goal pursuit.…”
Section: Goal Pursuitsupporting
confidence: 56%
See 2 more Smart Citations
“…Specifically, after MS (vs. control) these individuals squeezed a hand dynamometer (which measures grip strength) harder than prior to MS. MS clearly made these individuals put more effort into this goal-relevant task. Other work has similarly shown that MS enhances basketball performance [36] and improves performance on academic tasks (e.g., reading comprehension) [37,38]. Taken together, this work suggests that the awareness of death may underlie the motivation to excel and is beneficial for goal pursuit.…”
Section: Goal Pursuitsupporting
confidence: 56%
“…For one, terror management processes can lead individuals to put more effort into valued tasks, which helps fuel culturally valuable achievements. For example, MS has been shown to enhance strength output [35], sports performance [36], and academic performance [37,38] when those domains are culturally relevant. Likewise, terror management processes can fuel additional prosocial responses.…”
Section: Social Groups and Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the question for future research. It is also recommended to replicate our findings on other effects related to TMT, like higher performance in sports (Zestcott et al 2016) or more positive attitude towards killing the animals (Lifshin et al 2017). …”
Section: Limitationsmentioning
confidence: 87%
“…One hypothesis that has guided much of the TMT literature is the mortality salience hypothesis (Greenberg et al, 1990), which posits that if certain psychological structures (e.g., cultural worldviews and self-esteem) serve to shield against the awareness of death, then increased mortality salience (MS) should motivate people to defend and affirm them. For example, research has found that MS increases selfesteem striving and performance in worldviewrelevant domains such as academics and athletics (e.g., Landau et al, 2009;Peters et al, 2005;Williams et al, 2012;Zestcott et al, 2016). Moreover, research has shown that MS motivates people to defend cultural norms and national identity (Rosenblatt et al, 1989;Greenberg et al, 1990Greenberg et al, , 2003 as well as uphold culturally-valued goals and ideals (e.g., Greenberg et al, 1992Greenberg et al, , 2010Jonas et al, 2013;Gailliot et al, 2008).…”
Section: Terror Management Research and Docomentioning
confidence: 99%